Pengaruh Inflasi, Kurs, Bi Rate, IHSG, Volume Perdagangan terhadap Return Saham dengan Harga Saham Sebagai Variabel Moderasi - Intan Dwi Oktavia; Refalinda Hayu Seantemat Maurany; Adinda Dwi Novita Sari; Aditya Wardana; Ashabul Firdaus; Achmad Miftachul Huda (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
This quantitative study analyzes the effects of inflation, rupiah exchange rate, BI Rate, JSX Composite (IHSG), and trading volume on the stock return of PT Bank Central Asia Tbk (BBCA) for the 2021–2025 period, with stock price as a moderating variable. Using Moderated Regression Analysis (MRA) based on official secondary data, the partial test results show that inflation, rupiah exchange rate, BI Rate, IHSG, and trading volume have no significant effect on BBCA's stock return. In the moderation test, stock price is proven to only moderate the effect of the rupiah exchange rate on stock return, while showing no moderating role for the other variables. However, simultaneously, the model with the moderating variable explains changes in stock return better than the model without moderation. In conclusion, the company's internal fundamental factors and specific stock characteristics play a much more dominant role in influencing BBCA's stock return compared to macroeconomic factors, making these findings a strategic consideration for investors in capital market decision-making.